The Effect of Task Based Language Teaching on the Teaching Practice of Pre Service English Teacher - Ma'mun, Nadiah (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2018)
This present study investigated the effect of Task-Based Language Teaching (TBLT) on the teaching practice of pre-service English teacher. The research method used to study was experimental research with one group design. The sample of the research was 25 students of Microteaching class at English Education Department. The data were collected through the Performance Test of teaching practice as the instrument of the research. After conducting the pre-test of the Performance test of teaching practice and giving the treatment by using TBLT and the post-test. The result of post-test is higher than pre-test. It happened after the researcher gave treatments using TBLT to the pre-service English teacher. The researcher used the t-test formula to discover the significant difference between the teaching practice of the pre-service English teacher and the use of TBLT. The score of t-test was 8.90, higher than t-table. Thus, it could be concluded that there was a significant difference before and after being taught by using TBLT. The result showed that it had a positive effect.